(untitled) - Eusebius of Caesarea c. 260-340; Cruise, C.F. (Peabody, MA Hendrickson, 1998)
Includes the Loeb numbering system as a reference to the original Greek. Includes index.
Keywords: Eusebius of Caesarea, -- c.260-340; Church history -- primitive and early church, ca. 30-600 -- sources